PENGARUH METODE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR EKONOMI - Zainal, Vetri Yanti (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2020)
The main problem in this study is the low learning outcomes due to several factors including students being less actively involved in learning economics which requires a better process of understanding lessons. However, the learning method applied by the teacher still does not improve the learning outcomes of students in Economics. The research objective was to determine and describe whether there was an effect of the Think Pair Share (TPS) method on economic learning outcomes. The method used in this research is the experimental method. The population in this study were students of class X.IPS, totaling 80 students, where the sample consisted of class X.IPS 1 as the experimental class, amounting to 40 people and X.IPS 2 as the control class, amounting to 40 people. Based on the hypothesis testing and the results of the data analysis that has been done, the writer can conclude that: The results of the calculation of thit = 4.04> tdaf = 2.00, it is concluded that there is an effect of the Think Pair Share (TPS) method on economic learning outcomes. The average learning outcome in the experimental class taught using the Think Pair Share (TPS) method was higher than the control class